Effect of gamma irradiation on the physical stability of DPPC liposomes - Liyana Mohd Ali Napia; Irman Abdul Rahman; Mohd Yusof Hamzah; Faizal Mohamed; Hur Munawar Kabir Mohd; Intan Syakeela Ahmad Bastamam; Shamellia Sharin; Norsyahidah Mohd Hidzir; Shahidan Radiman (Penerbit Universiti Kebangsaan Malaysia, 2018)
Unilamellar liposomes composed of dipalmitoylphosphatidylcholine (DPPC) were prepared by the reverse-phase evaporation method and extrusion through a polycarbonate membrane filter. Liposomes at 0.7 mg/mL lipid concentration in deionized water were exposed to gamma irradiation at a dose in the range 0.5 to 25 kGy. Gamma irradiation of liposomes resulted in the degradation of DPPC lipids into free fatty acids, lysophosphatidylcholine and 1,2-palmitoyl-phosphatidic acid (DPPA). The effect of gamma irradiation towards the physical stability of liposomes was investigated by means of dynamic light scattering (DLS), transmission electron microscopy (TEM) and zeta potential analysis. From the DLS analysis, no significant changes were observed in the hydrodynamic size of liposomes. TEM images indicate that the liposomes surface became smoother and rounder as higher irradiation doses were applied. Zeta potential analysis showed that gamma irradiation of DPPC liposomes at radiation doses as low as 0.5 kGy resulted in a drastic rise in the magnitude of the zeta potential. The results also demonstrate that gamma irradiation of liposomes suspension enhanced the overall stability of liposomes. Hence, it can be concluded that gamma irradiation on DPPC liposomes may potentially produce liposomes with higher stability.